Mechanistic Insight into Apoptotic Induction in Human Rhabdomyosarcoma and Breast Adenocarcinoma Cells by Chnoospora minima: A Sri Lankan Brown Seaweed - Thilina Lakmini Gunathilaka (MDPI AG, 2021)
The current study determined the cytotoxic and apoptotic potential of the polyphenol-rich methanol extract of Chnoospora minima (C. minima) and its fractions against human breast adenocarcinoma (MCF-7) and rhabdomyosarcoma (RMS) cells. MTT and neutral red assays were used to determine cytotoxicity. The clonogenic assay evaluated the antineoplastic activity, while the apoptotic activity was determined by cellular morphological changes, caspase 3/7 activity, and DNA fragmentation. Morphological alterations in apoptosis were observed by an inverted phase-contrast microscope and Hoechst 33342 staining methods. The total phenolic, flavonoids, alkaloids, and antioxidant activity in the hexane and chloroform fractions were determined, based on their cytotoxic activity. The hexane fraction of C. minima effectively reduced the cell growth that is concentration-dependent in human RMS and MCF-7 cell lines. It also exhibited low cytotoxicity on Vero cells. The characteristic cellular and nuclear apoptotic morphological features were observed. A noticeable caspase 3/7 activation and the fragmented DNA were detected only in the hexane fraction treated RMS cells, whereas MCF-7 cells showed low caspase 3/7 activation due to a lack of caspase 3 and no evidence of having a typical ladder pattern of apoptosis. Further analysis revealed that the hexane fraction-treated RMS cells upregulated the p53 gene twofold (2.72) compared to the p21 (0.77) gene, whereas in the MCF-7 cells, a 2.21-fold upregulation of p53 was observed compared to the p21 (0.64) gene. The hexane fraction exhibited moderate total phenolics, flavonoids, alkaloids content, and antioxidant activity. According to the different antioxidant mechanisms, hexane and chloroform fractions showed the highest antioxidant activities by FRAP and ORAC assays, respectively. GC-MS analysis of hexane fraction revealed the presence of methyl tetradecanoate (38.314%) as the most abundant compound. The study’s findings highlighted that the non-polar compounds present in the hexane fraction of C. minima suppressed cell proliferation and induced apoptosis-mediated cell death in RMS and MCF-7 cells, mainly via the activation of the p53 gene. Hence, the isolation of compounds is warranted. However, more studies are required to understand the mechanistic insights of these observations.